Moderate-dose caffeine enhances anaerobic performance without altering hydration status - Mor, Ahmet; Acar, Kürşat; Alexe, Dan Iulian; Mor, Hakkı; Abdioğlu, Mekki; Man, Maria Cristina; Karakaș, Fatih; Waer, Fatma Ben; Yılmaz, Ali Kerim; Alexe, Cristina Ioana (Frontiers in Nutrition, 2024)
The effects of direct nutritional supplements on athletic performance are still being investigated and arouse curiosity. Only one study in the literature was found that investigated the kicking speed performance of futsal players following low-dose caffeine supplementation (3 mg/kg); thus, the question of whether caffeine supplementation improves kicking speed as well as essential physical parameters in soccer players is still controversial. Therefore, the aim of this study was to determine the effect of caffeine supplementation on vertical jump (VJ), sprint, reaction time, balance, change of direction (COD), and ball-kicking speed in soccer players. In a double-blind, cross-over design, nine moderately trained male soccer players (21.11±2.02 years, 171.22±6.14 cm, 71.78±10.02 kg) consumed caffeine (6 mg/kg) or a placebo 60 min before completing balance, reaction time, vertical jump, agility, 30-m sprint, and ball-kicking speed tests. Greater VJ height (p=0.01) and power (p=0.08), and faster completion time according to the Illinois Agility Test (p=0.08) were found following caffeine supplementation compared to placebo. Elapsed time (p=0.01), average (p=0.01) time, and the slowest reaction times (p=0.016) were significantly reduced after caffeine consumption compared to placebo supplementation. Caffeine intake significantly improved VJ, agility, and reaction time (p<0.05) but did not affect 30m sprint, ball-kicking speed, balance, and RPE values in soccer players (p>0.05). Although non-significant, caffeine intake also improved sprint (0.67%) and ball kicking (2.7%) performance percentages. Also, caffeine consumption did not induce dehydration, and the athletes' body hydration levels were normal. These findings support the use of caffeine supplementation as an effective nutritional ergogenic aid to enhance anaerobic performance, at least for vertical jumps, COD speed, and reaction time, in trained male soccer players.